Oral myofunctional and electromyographic evaluation of the anterior suprahyoid muscles and tongue thrust in patients with Class II/1 malocclusion submitted to first premolar extraction - Denize Ramirez de Souza; Tatiana Adamov Semechini; Lucio Benedito Kröll; Fausto Berzin (University of São Paulo, 2007)
OBJECTIVE: The aim of this study was to assess the existence of myofunctional alterations before and after first premolar extraction in Class II/1 malocclusion patients that could endanger the long-term dental arch stability. MATERIAL AND METHODS: The study was performed by means of morphological, functional and electromyographic analyses in 17 Class II/1 malocclusion patients (group T) and 17 Class I malocclusion patients (group C), both groups with 12-30-year age range (mean age: 20.93 ± 4.94 years). RESULTS: Data analyzed statistically by Student's t-test showed a significant decrease in the maxillary and mandibular dental arch perimeters after orthodontic treatment (p<0.05). The Kruskal-Wallis test analyzed data from tongue posture at rest and during swallowing, not showing significant differences after treatment (groups Tb and Ta) (p>0.05). However, group T differed significantly from group C (p<0.05). The electromyographic data showed that the anterior right and left suprahyoid muscles acted synergistically in both groups, while having a lower myoelectric activity in group T during swallowing. CONCLUSIONS: Myofunctional alterations observed after the orthodontic treatment in Class II/1 malocclusion seemed to jeopardize the long-term orthodontic stability, making recurrence possible. Further research should be conducted to compare electromyographic data before and after orthodontic treatment in order to corroborate the results of the present investigation.